Teachers’ attitudes and self-efficacy toward inclusive education in mainland China: a meta-analysis - Yanlin Long; Umesh Sharma; Pearl Subban (Cogent Education)
Classroom teachers’ inclusive practices that address students’ diverse needs are vital for successful inclusive education reform. Given that teachers’ attitudes and self-efficacy beliefs toward inclusive education are arguably pivotal factors in influencing the implementation of inclusive education, this meta-analysis synthesized the research on Chinese teachers’ attitudes and self-efficacy toward inclusion. Applying rigorous inclusion criteria,16 qualifying studies from 2010 to 2024 covering 10361 Chinese teachers were identified. Three random-effect models revealed that Chinese teachers generally hold moderately positive attitudes (g = 0.42) and high self-efficacy toward inclusion (g = 1.31) over the past ten years. Furthermore, Chinese teachers’ attitudinal and efficacy beliefs were moderately correlated ([Formula: see text] = 0.49). Following meta-regression analysis revealed that the correlation between attitudes and self-efficacy has seen a slightly positive trend over the past decade. Moreover, female teachers had marginally higher self-efficacy toward inclusion than their male counterparts. However, teacher type (pre-service or in-service teacher), students’ type of disability, and school-level factors did not significantly predict teachers’ attitudes, self-efficacy, or their correlation. Understanding the status of teachers’ attitudes, self-efficacy, and the influencing factors could foster their use of inclusive practices in regular classrooms.